2017
DOI: 10.1007/s00005-017-0480-8
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Associated Macrophages as Target for Antitumor Therapy

Abstract: It is well known that the microenvironment of solid tumors is rich in inflammatory cells that influence tumor growth and development. Macrophages, called tumor-associated macrophages (TAMs), are the most abundant immune cell population present in tumor tissue. Several studies have demonstrated that the density of TAMs is associated with a poor prognosis and positively correlates with tumor growth. Several studies have proved that TAMs may activate and protect tumor stem cells, stimulate their proliferation as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
132
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 176 publications
(145 citation statements)
references
References 158 publications
(175 reference statements)
2
132
0
Order By: Relevance
“…As M2‐like TAMs highly stimulate tumor progression, targeting TAM polarization is an interesting potential therapeutic strategy. Several strategies have been proposed to reprogram TAMs toward M1 macrophages: antibody‐mediated activation of costimulatory CD40, blocking of IL‐10, or targeting intracellular signaling molecules . A novel approach to reprogram macrophages is using histone acetyl deacetylase (HDAC) inhibitors, which cause changes in the transcriptional profile of the macrophages and limits tumor growth .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As M2‐like TAMs highly stimulate tumor progression, targeting TAM polarization is an interesting potential therapeutic strategy. Several strategies have been proposed to reprogram TAMs toward M1 macrophages: antibody‐mediated activation of costimulatory CD40, blocking of IL‐10, or targeting intracellular signaling molecules . A novel approach to reprogram macrophages is using histone acetyl deacetylase (HDAC) inhibitors, which cause changes in the transcriptional profile of the macrophages and limits tumor growth .…”
Section: Resultsmentioning
confidence: 99%
“…A novel approach to reprogram macrophages is using histone acetyl deacetylase (HDAC) inhibitors, which cause changes in the transcriptional profile of the macrophages and limits tumor growth . A comprehensive overview of studies performed targeting TAMs for antitumor therapy has recently been provided in a review by Sawa‐Wejksza and Kandefer‐Szerszen . Since macrophage metabolism is strongly connected to its functionality, metabolic reprogramming of macrophages might be an elegant way to skew the polarization of TAMs toward an antitumor phenotype.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have demonstrated that the density of TAMs is associated with a poor prognosis and enhanced tumour growth [11,31,32]. Furthermore, TAM-derived cytokines, such as IL-6, IL-1, IL-8, TNF-α, CCL-17 and CCL-22, significantly contribute to proliferation, immunosuppression, and angiogenesis in support of tumour growth and metastasis [32].…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages, especially so-called tumour-associated macrophages (TAMs), are the most abundant immune cell population present in tumour tissues, and they are usually marked by CD68 [11,12]. The polarization of macrophages into tumour-suppressive M1 or tumour-promoting M2 types is a fundamental event in the establishment of the tumour microenvironment, and ample evidence has indicated that TAMs are primarily M2 polarized, which act as pro-tumourous factors in many types of human tumours [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Current macrophage‐targeted therapies under development aim to: 1) inhibit monocyte/macrophage recruitment, 2) deplete macrophages, or 3) activate macrophage anti‐tumor functions ( Figure and Table 1 ). There exists some controversy about whether TAMs are derived from blood‐circulating monocytes or from infiltrating peripheral tissue macrophages . However, inhibiting monocyte recruitment and their subsequent maturation into TAMs by blocking the C‐C motif chemokine ligand 2 (CCL2)–C‐C motif chemokine receptor 2 (CCR2) axis has indeed improved survival in tumor‐bearing mice .…”
Section: Synthetic Biomaterials To Target Tams In Cancer By Systemicmentioning
confidence: 99%